Clove essential oil-supported disposable in-tip cellulose paper (DICP) device for facile extraction of anesthetic drugs from postmortem samples: a white analytical toxicology (WAT) approach - Jain, Rajeev; Shivankar, Bhavana R.; Krishnamurty, Sailaja; Al-Khateeb, Lateefa A.; Sheetal, Sarah; Alharthi, Sarah (Sustainable Chemistry and Pharmacy, 2025)
A novel disposable in-tip cellulose paper (DICP) device, enhanced with clove essential oil (CEO), was developed for the extraction of four anesthetic drugs (lidocaine, prilocaine, ropivacaine, and bupivacaine) from postmortem blood and urine samples. The DICP device, equipped with 1 x 3 cm CEO-impregnated cellulose paper (CP) strips (prepared via a simple dip-coating process), is attached to a 1000 mu L micropipette. The findings from density functional theory (DFT) study reveals that CEO-impregnated cellulose demonstrates stronger and more diverse interactions with anesthetic drugs, as evidenced by more negative adsorption energy (-0.62 eV) and enhanced non-covalent interactions compared to cellulose alone. The procedure involves aspirating and dispensing diluted biological samples through the DICP device for 30 cycles, adsorbing the analytes onto the CEO-impregnated CP strips. The adsorbed analytes are subsequently eluted with 0.5 mL of ethyl acetate through 40 aspirating-dispensing cycles and analyzed by GC-MS. The method achieved limits of quantification as low as 0.01 mu g/mL, with intra-day and inter-day precisions below 10.2 % and 14.6 %, respectively, and accuracy ranging from 90.5 % to 110.7 %. Relative recoveries ranged from 66 % to 87.6 %, while matrix effects remained consistently below 11.9 %. The DICP-GC-MS method demonstrated exceptional sustainability, achieving a whiteness score of 97.2 %, underscoring its alignment with green analytical chemistry principles and operational simplicity. Applicability was demonstrated through the successful analysis of postmortem cardiac blood in a suspected anesthetic drug overdose case, highlighting its potential as a robust, high-throughput, and eco-friendly approach for routine forensic toxicological screening.
Keywords: Anesthetic drugs; Clove essential oil; Disposable in-tip cellulose paper (DICP) device; Green sample preparation; White analytical toxicology (WAT)